Inaccuracy within Online Journalism in Indonesia - Emeraldien, Fikry Zahria; Sugihartati, Rahma; Rahayu, Titik Puji (Jurnal The Messenger, 2021)
Many scholars have conducted studies on the accuracy of the news media, such as newspaper, television, and magazine, but not online media. In fact, online media is a significant news media in the moment, especially in Indonesia. Online press companies are even the largest press companies in Indonesia compared to newspapers, radio, and television. Therefore, this study is conducted to measure the inaccuracies that occur in news in online news media. Researchers examined 63 online journalistic media that have been administratively and factually verified by the Dewan Pers (Press Council). It uses a content analysis method by coding the headlines in Indonesian online journalistic media. This study finds online mass media categories based on the theme segmentation, namely: 1) general, 2) economics, technology, and business, 3) sports, 4) politics, law, and crime, 5) lifestyle and entertainment, and 6) regional. The results of this study indicate that the inaccuracy of news in Indonesian online media is high. Media with economics, technology, and business most often make grammatical errors. This study also finds that speed does not only has an impact on grammatical inaccuracies, but also on unbalanced news reporting, where the imbalance in Indonesian online media news itself is very high.